Identidad en transición: relaciones de género en los consejos provinciales de Huancayo y Jauja entre 2011 y 2014 - Navarro Véliz, Alejandra (2021)
This article explores the interactions between female and male councillors in two Peruvian municipal councils from a gender perspective. In the first place, some figures about women’s political participation in the councils under analysis are presented, followed by a brief introduction of the main findings of the academic literature about the topic of interest. In second place, it introduces the main concepts of feminist theory in political science that will be used to understand the relationships between the authorities, focusing on the sexual division of labour (SDL). In third place, the main features of the political trajectories, both men’s and women’s, are presented, as well as how they are shaped by individual, family and institutional factors that are mediated by gender. The article concludes that the trajectories of female and male councillors are more similar than different. However, there are differences in terms of how they value their own experience. It was also found that female authorities still confront limitations to find a balance between the time spent in politics and in family life; in other words, between productive and reproductive time. This fact can lead towards the construction of an in-transit-identity, to the extent that both women and men face a transformation in paradigms about power exercise, political leadership, and the divide between private and public.